2022
DOI: 10.2147/dddt.s363286
|View full text |Cite
|
Sign up to set email alerts
|

Orexin-A Reverse Bone Mass Loss Induced by Chronic Intermittent Hypoxia Through OX1R-Nrf2/HIF-1α Pathway

Abstract: Background: Recent studies suggest that there is a potential connection between obstructive sleep apnea (OSA) and osteoporosis through dysregulation of bone metabolism. Orexin-A, a neuroprotective peptide secreted by the hypothalamus, is at a lower level in the plasma of OSA patients, which regulates appetite, energy expenditure and sleep-wake states. However, the protective effect of orexin-A on bone metabolism in OSA is unclear. Purpose: To investigate whether the activation of OX1R by orexin-A can reverse b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The hypothalamus is involved in the pathogenesis of osteoporosis. According to research, the hypothalamus is involved in bone metabolism in women with or without ovarian function loss 25 . Our study found that serum levels of GnRH and FSH were higher in POI rats than in normal rats, and that YWD could reduce serum levels of GnRH and FSH in POI rats.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothalamus is involved in the pathogenesis of osteoporosis. According to research, the hypothalamus is involved in bone metabolism in women with or without ovarian function loss 25 . Our study found that serum levels of GnRH and FSH were higher in POI rats than in normal rats, and that YWD could reduce serum levels of GnRH and FSH in POI rats.…”
Section: Discussionmentioning
confidence: 99%
“…There are many people with OSA in the world, and morbidity is rising and mostly occurs in middle-aged and elderly men (19). OSA is a complex somatic disease that has a significant impact on quality of life, mortality rate, and long-term cardiovascular outcomes (20).…”
Section: Discussionmentioning
confidence: 99%
“…Orexins play pivotal roles in regulating feeding behavior, energy balance, sleep-wake cycles, autonomic nervous system function, and neuronal survival [166]. Multiple studies have demonstrated that Orexin-A can upregulate the expression of HIF-1 by inhibiting VHL or E3 ubiquitin ligase activity [167][168][169]. In PD pathogenesis, mitochondrial dysfunction may lead to reduced oxygen consumption, thereby activating prolyl hydroxylase and decreasing HIF-1α levels, which subsequently reduces the expression of several transcription factors implicated in protecting the brain against oxidative stress.…”
Section: Modulation Of Hif Activity As a Therapeutic Approach To Neur...mentioning
confidence: 99%